Study of Loss Mechanisms Using Half-Cell Measurements in a Regenerative Hydrogen Vanadium Fuel Cell - Dewage,HH; Yufit,V; Brandon,NP (Journal of the Electrochemical Society, 2015)
The positioning of reference electrodes in redox flow batteries without disturbing the cell operation represents a great challenge. However decoupling anode and cathode processes is crucial in order to fully understand the losses in the system so it can be further optimized. The feasibility of a regenerative fuel cell based on an V(IV)/V(V) electrolyte and hydrogen gas has previously been demonstrated. In this investigation, using electrochemical impedance spectroscopy, the various losses of the cathode, anode and whole cell were established using an alternative reference electrode set-up. The findings showed that the largest irreversible losses under the conditions tested arose from diffusion limitations in the cathode and the effect of vanadium crossover and therefore adsorption onto the platinum layer of the hydrogen electrode leading to higher losses on the anode. These results highlight the potential for further improvement and optimization of cell design and materials for both electrodes in the Regenerative Hydrogen Vanadium Fuel Cell.